2013
DOI: 10.1002/mats.201370013
|View full text |Cite
|
Sign up to set email alerts
|

Macromol. Theory Simul. 6∕2013

Abstract: Cover: Using dilatometry combined with shear flow at conditions comparable to realistic processing conditions, a flow induced crystallization model is employed for the kinetics of quiescent nucleation, flow enhanced nucleation, fibrillar growth, and the time evolution of the dimensions of the resulting crystalline structures. Three important model parameters are determined over a broad range of temperatures, pressures, and shear rates; pre‐factors to the creation rate of nucleation and to the shish growth rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Recently, Zhong et al, 36 confirmed the validity of the approach of van Meerveld et al working with a different polymer (PLA). Moreover, van Erp et al, 37 (2) Effect of flow on crystalline development. One piece of evidence is the presence of highly ordered crystalline phase(s) in a sample solidified under the effect of flow.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Zhong et al, 36 confirmed the validity of the approach of van Meerveld et al working with a different polymer (PLA). Moreover, van Erp et al, 37 (2) Effect of flow on crystalline development. One piece of evidence is the presence of highly ordered crystalline phase(s) in a sample solidified under the effect of flow.…”
Section: Methodsmentioning
confidence: 99%
“…In the model introduced by Steenbakkers et al [13], and used in various studies by Peters and coworkers [51,[53][54][55], the enhancement of nucleation due to flow was ascribed solely to the dependence on stretching, rather than the combination of stretching and orientation that is…”
Section: Assessment Of Conformation-based Fen Modelsmentioning
confidence: 99%
“…Recent developments in shear‐induced crystallization (SIC) have demonstrated the existence of three regimes which, for the same polymer at the same temperature and pressure, occur on increasing the flow intensity: (i) the effect of flow upon the final morphologies and crystallization kinetics is negligible, (ii) the flow causes a strong enhancement of crystallization kinetics, increasing the number of nuclei and thus the average dimension decreases, but the spherulitic morphology is kept, (iii) the flow deeply influences both morphology and kinetics by causing the formation of fibrillar structures in the polymer melt. However, apart from a qualitative understanding of the phenomena, a quantitative description of the phenomena is still discussed and it is currently under investigation …”
Section: Introductionmentioning
confidence: 99%
“…However, apart from a qualitative understanding of the phenomena, a quantitative description of the phenomena is still discussed and it is currently under investigation. [9][10][11][12][13][14] In particular, the TU/e research group in Eindhoven developed novel experimental devices in order to investigate the temperature and pressure dependence in combination with applied shear flow. A shear slit device, [9] namely a Multipass Rheometer, was adopted to perform experiments under well-defined conditions to study the effect of shear flow on structure formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation